Adolescent female learners experience and knowledge of human rights at a secondary school in a Sub – district of Cape Town, South Africa - Swartz, Deirdre (2014)
Magister Artium (Human Ecology) - MA(HE) === Human Rights have been the focus of much debate in recent years. It is read about in biblical contexts and extensively written about and researched globally,nationally and locally. South Africa is especially recognised as a country trying to adhere to human rights recommendations since after experiencing years of “apartheid” and human rights violations. South Africa is proud to introduce a sixteen-year democracy and a constitution respected by the global society.As South Africa embarks on a period of transformation, women who were historically marginalised are encouraged through education to demand their right to know that their human rights be recognised. The adolescent female in her educational environment is socialized to recognise her basic human rights and, through education,she is able to embrace them and demand that they be upheld.The adolescent female learner within the South African context is the focus of this study as we explore her knowledge and experiences’ of human rights at school. The study also attempts to explore the schools role in providing adequate facilitation for the adolescent female learner to gain sufficient knowledge about her basic human rights.Both quantitative and qualitative research methodology were used in this study. A sample of 12 adolescent female learners was purposively selected. The study was conducted at a Secondary School in the Central Sub-district of Cape Town in the Western Cape. The questionnaire was standardized by testing the questions on learners and the Life Orientation educator of another school. A thematic analysis was used to analyse the audio taped data from the interviews.The key findings were that the adolescent female perceives human rights as being equal and being human amongst other humans but that their human rights are violated at school. It was also found that knowledge about human rights changed the attitudes and behaviour of the adolescent female learners in creating higher self confidence, the ability to stand up for themselves, have a positive self image and an understanding and appreciation for other cultures.The recommendations from this study includes: that the adolescent female learners need to internalize their basic human rights and then demand that these rights be upheld. The integration of human rights concepts within other learning areas or subjects in the school curriculum were additional recommendations.